Menaksir Nilai Ekonomi Objek Wisata Taman Manneken Manokwari : Aplikasi Individual Travel Cost Method - Dedi Riantoro (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2021)
Economic assessment of a tourist attraction, both natural and artificial, is very important for planning sustainable environmental management. The plan aims to maintain the development capital so that it can be managed as a source of regional income and also to improve the welfare of the community. On the other hand, the management of tourism objects can be used to improve the regional economy without the need to exploit its natural resources. This research was conducted at Manneken Park, an artificial tourism object located in Prafi District, Manokwari Regency. The study focused on the number of individual travel costs and the economic value of the tourism object using descriptive research methods with survey techniques involving 100 respondents as resource persons. By using the Individual Travel Cost Method (ITCM), the results show that the average travel cost is Rp. 692,120, - and the economic value of tourism objects is Rp. 6,925,795.703,-. This indicates that the economic benefits received by tourists to travel to the Manneken Park attraction are greater than the costs incurred. The intended economic benefits are in the form of benefits in the form of comforts such as getting peace, beauty, and satisfaction.